Estimación del Error en un Medidor de Turbina con Insuficientes Tramos Rectos - Ortiz Medel, Josefina; Ramírez Navarro, Francisco; Martínez González, Francisco; Pedroza González, Edmundo (Acta Universitaria, 2005)
In agricultural pumping plants flowmeters are frequently installed with insufficient straight sections of pipe both upstream and downstream from the meter, in order to meet the established installation specifications. It has been found that flowmeter manufacturers do not know the error rate in flow measurements under these no optimal conditions. In 1998, Hanson found that a propeller flowmeter had an error of 3,5 % when it was installed in a position a distance of two pipe diameters downstream from an elbow. This project investigated the performance of a turbine flowmeter under no optimal upstream and downstream conditions (conditions not considered by Hanson). Experiments were carried out in the Hydraulic Laboratory of the University of Guanajuato. Measurements were made in different flowmeter positions considering different flow rates. Results from this project showed that the flowmeter does not have a large error, even if it is installed in an incorrect position. However, lowest error rate is obtained when it was installed in the position recommended by the manufacturer.
Keywords: Array; Array